2001
DOI: 10.1128/aac.45.4.1086-1093.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Metabolites of the Human Immunodeficiency Virus Protease Inhibitor Nelfinavir in Humans: Structural Identification, Levels in Plasma, and Antiviral Activities

Abstract: Nelfinavir mesylate (Viracept, formally AG1343) is a potent and orally bioavailable human immunodeficiency virus (HIV) type 1 (HIV-1) protease inhibitor (K i ‫؍‬ 2 nM) and is being widely prescribed in combination with HIV reverse transcriptase inhibitors for the treatment of HIV infection. The current studies evaluated the presence of metabolites circulating in plasma following the oral administration of nelfinavir to healthy volunteers and HIV-infected patients, as well as the levels in plasma and antiviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 19 publications
2
84
0
Order By: Relevance
“…Two metabolites of nelfinavir were detected after incubating with rat hepatocytes, previously identified as M1 by Zhang et al (2001). [Saquinavir]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two metabolites of nelfinavir were detected after incubating with rat hepatocytes, previously identified as M1 by Zhang et al (2001). [Saquinavir]…”
Section: Resultsmentioning
confidence: 99%
“…The retention times were approximately 3.4 (verapamil) and 3.5 (saquinavir) min. Nelfinavir and its metabolite (M1) (Zhang et al, 2001) and ritonavir and its metabolites (M1, M2, M9, and M11) (Denissen et al, 1997) together with verapamil (internal standard) were separated using the same system as for saquinavir except that the initial mobile phase of 90% 0.001 M ammonium acetate/10% acetonitrile was ramped linearly to 90% acetonitrile/10% 0.001 M ammonium acetate from 1 to 4 min. The retention times were approximately 3.2 (verapamil), 3.3 (nelfinavir-M1), 3.4 (nelfinavir), 3.9 (ritonavir-M11), 4.1 (ritonavir-M2 and ritonavir-M9), and 4.6 (ritonavir and ritonavir-M1) min.…”
Section: Chemicalsmentioning
confidence: 99%
“…Subjects received the following treatments: period 1 (days 1-10), 1875 mg nelfinavir plus 200 mg ritonavir to be taken once daily at 23.00 h with a light snack of around 300 kcal; period 2 (days [11][12][13][14][15][16][17][18][19][20], 1875 mg nelfinavir plus 200 mg ritonavir and 600 mg efavirenz to be taken once daily at 23.00 h with a light snack (around 300 kcal). Blood samples were collected throughout a 24-h period on days 10 and 20 following a light meal of 315 kcal.…”
Section: Methodsmentioning
confidence: 99%
“…CYP3A4 is mainly responsible for the metabolism of nelfinavir [10]. However, the formation of the virologically active [11] metabolite nelfinavir-hydroxy-t -butylamide (designated M8) is primarily dependent on CYP2C19 [12]. M8 is subsequently metabolized by CYP3A4 into inactive metabolites [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nelfinavir (NFV) (Figure 14) is biotransformed in the liver into three major metabolites, identified as nelfinavir-hydroxy-t-butyl-amide (66), 3,4-dihydroxy-nelfinavir (67) and 3-methoxy-4-hydroxy-nelfinavir (68) . Compound 66 shows antiretroviral activity in vitro comparable to that of NFV, contributing to its oral activity in anti-HIV therapy, while 68 showed low activity (Zhang et al, 2001;Hirani, Raucy, Lasker, 2004). It has been shown that CYP3A4 is involved in the formation of metabolites 67 and 68, while 66 is produced by CYP2C19 (Wu et al, 1998;Lillibridge et al, 1998;Khaliq et al, 2000).…”
Section: Protease Inhibitors (Pis)mentioning
confidence: 99%